Frequency of different human mollicutes species in the mucosa of the oropharynx, conjunctiva, and genitalia of free-ranging and captive capuchin monkeys (Cebus spp.) - Neto, Renata L.; Marques, Lucas M.; Guimarães, Ana Márcia S.; Yamaguti, Mauricio; Oliveira, Rosangela C.; Jardim Júnior, Elerson Gaetti [UNESP]; Medina, Aziz O.; Sanfilippo, Luis F.; Timenetsky, Jorge (Wiley, 2013)
This study is the first to evaluate the occurrence of several Mollicutes species in Brazilian capuchin monkeys (Cebus spp.). Mollicutes were detected by culture and polymerase chain reaction (PCR) in samples of the oropharyngeal, conjuctiva, and genital mucosae of 58 monkeys. In the oropharynx, Mollicutes in general (generic PCR to the Class), and those of the genus Ureaplasma (genus PCR), were detected in 72.4% and 43.0% of the samples, respectively. The identified species in this site included: Mycoplasma arginini (43.1%), M. salivarium (41.4%), and M. pneumoniae (19.0%). Both Ureaplasma and Mycoplasma are genera of the order Mycoplasmatales. In the preputial/vaginal mucosa, PCR detected Mollicutes in general in 27.58% of the samples, the genus Ureaplasma in 32.7%, the species M. arginini in 8.6%, and Acholeplasma laidlawii of the order Acholeplasmatales in 1.7% In the conjunctiva, Mollicutes in general were detected in 29.3% of the samples, with 1.7% being identified as A. laidlawii. Culturing was difficult due to contamination, but two isolates were successfully obtained. The Mollicutes species of this study provided new insights into these bacteria in Brazilian Cebus. Studies are lacking of the actual risk of Mollicutes infection or the frequency at which primates serve as permanent or temporary reservoirs for Mollicutes. In the present study, the samples were collected from monkeys without clinical signs of infection. The mere presence of Mollicutes, particularly those also found in humans, nevertheless signals a need for studies to evaluate the impact of these microorganisms on the health of non-human primates (NHPs) and the possibility of cross-species transmission between NHPs and humans. © 2013 Wiley Periodicals, Inc.
Keywords: Cebus; Conjunctiva; Mollicutes; Oropharynx; Prepuce; Vagina; Acholeplasma laidlawii; Acholeplasmatales; Bacteria (microorganisms); Haplorhini; Mycoplasma; Mycoplasma arginini; Mycoplasma pneumoniae; Mycoplasma salivarium; Mycoplasmatales; Primates; Ureaplasma